Religion and Prison: An Overview of Contemporary Europe - Martínez-Ariño, Julia; Zwilling, Anne-Laure (Boundaries of Religious Freedom: Regulating Religion in Diverse Societies, 2020)
Chapter1. Management of Religious Diversity in Austrian Prisons (Wolfram Reiss) -- Chapter2. Religion and Prisons in the Belgian Law (Stéphanie Wattier, Louis-Léon Christians) -- Chapter3. Religion in Prisons: Bulgaria (Daniela Kalkandjieva) -- Chapter4. Religion in Prison in Croatia: Equal Access in a Predominantly Catholic Society (Sinisa Srinszak) -- Chapter5. Prison and Religion in the Czech Republic (Záboj Horák) -- Chapter6. Prison and Religion – The Czech Republic (Jan Váně) -- Chapter7. Religion and Prisons in Denmark (Niels Waldemar Vinding) -- Chapter8. Religion in Estonian Prisons since the 1990s (Ringo Ringvee) -- Chapter9. Religion in prisons in Finland (Sami Puumala) -- Chapter10. Worship in prison in France (Vincente Fortier) -- chapter11. Religion in German Prisons (Sarah Jahn) -- Chapter12. Religion in the Italian Prison System (Francesco Allicino) -- Chapter13 Position of Religion in the Penitentiary Institutions in Latvia (Anita Stasulane) -- Chapter14. Religion in Montenegrin Prisons (Nikola Šaranović) -- Chapter15. Oligopoly Dynamics in the Dutch Penitenriary System (Sipco Vellenga) -- Chapter16. Religion in the Norwegian Prison System (Helge Arsheim) -- Chapter17. Religious Care and Religious Practices in the Contemporary Polish Prison System (Michal Zawislack) -- Chapter18. Religion in Prisons in Romania: Historical, Legal and Sociological Aspects (Gabriel Birsan) -- Chapter19. Religion in Spanish Prisons: Socio-legal perspectives (Julia Martínez-Ariño) -- chapter20. Religions and Spiritualities in Switzerland: Institutional Analysis (Anaïd Lindemann) -- Chapter21. Religious Silent Retreat as Rehabilitation Treatment in Swedish Prisons (Per Pettersson) -- Chapter21. Religious Care in Turkish Prisons (Ahmet Erdi Öztürk) -- Chapter22. Prison and Religion in the United Kingdom (Andrew Todd) -- Chapter23. A Short Word on Religion in Prison in Russia (Michail Chakhov). .